Sintesis Senyawa 1,5-Difuril-1,4-Pentadien-3-On - Ismi Rahmawati (Fakultas Farmasi Universitas Setia Budi, 2011)
Modification on the curcumine structure by altering the Î²-diketon to monoketon resulting in the curcumine-analog compounds with antioxidan, antiinflamation, and antibacterial activity. The objectives of this research are to produce compound 1,5-difuril-1,4-pentadiene-3-one. The syntesis of the compounds used keton (aceton) and furfural as base materials and KOH as a catalyst in the akuades solvent. The purity test were carried out with thin layer chromatography, gas chromatography, and melting distance test. Structure elucidation was performed with IR spectrophotometer, H1-NMR and mass spectrometer analysis. The result of this study demonstrate that 1,5-difuril-1,4-pentadiene-3-one have been successfully synthesized and purified, and have chemical structure as expected. The yield of the synthesis yield is 85.99% and 60.13% is the result of recrystallization.